2020
DOI: 10.1111/jcmm.16066
|View full text |Cite
|
Sign up to set email alerts
|

TFE3‐PD‐L1 axis is pivotal for sunitinib resistance in clear cell renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) has become the most malignant tumour of kidneys in worldwide. 1 Clear cell renal cell carcinoma (ccRCC) is the most common subtype of RCCs, representing approximately 70% of all adult renal carcinomas. The other histologies mainly encompass papillary and chromophobe RCC. 2 The prognosis of ccRCC is poor: 30% of patients are metastatic at diagnosis and almost 30% of the remaining patients will develop metastasis detected during the follow-up. 3 With the continuous development of medic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We observed that the levels of miR-34a were significantly down-regulated in the resistant clones of all three cell lines. An increase in PD-L1 protein expression in response to transient sunitinib treatment has previously been reported in 786-O and A498 cell lines [17,54]. We extended these observations to the resistant clones of these cell lines, as well as to CD274 mRNA expression.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We observed that the levels of miR-34a were significantly down-regulated in the resistant clones of all three cell lines. An increase in PD-L1 protein expression in response to transient sunitinib treatment has previously been reported in 786-O and A498 cell lines [17,54]. We extended these observations to the resistant clones of these cell lines, as well as to CD274 mRNA expression.…”
Section: Discussionsupporting
confidence: 75%
“…These results suggest that ccRCC patients with VHL gene mutations (>50% of patients) [57] that do not express HIF1α (~70% of ccRCC patients [58]) could have an improved response to sunitinib treatment through targeting of PD-L1 by checkpoint inhibitor antibodies such as avelumab that already has FDA-approval for combination treatment in ccRCC [59]. Consistent with this hypothesis, Guo et al demonstrated that a combination of anti-PD-L1 and sunitinib significantly reduced tumour progression in vivo [17]. Indeed, although immunotherapy targeting the PD-1/PD-L1 axis shows great promise for ccRCC, only 15-25% of patients respond when given it as a monotherapy [60], and there is increasing movement towards combination therapy of antiangiogenic agents and immunotherapy [59,[61][62][63][64].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The sunitinib‐tolerant phenotype showed reduced inhibition of DNA synthesis under treatment, compared to the wild‐type confirming the activity of sunitinib on cell proliferation 36,37 . In various tumour entities, aberrant activation of MET and AXL has been described in terms of resistance to RAS–RAF–MEK, mammalian target of rapamycin (mTOR), VEGFR therapies 16,38,39 including sunitinib and sorafenib, 16,40 and, recently, immune evasion 41 . The activity of c‐MET‐downstream kinases, ERK ½, and AKT/S6K might also be related to enhanced cell survival and proliferation in 786‐O/S and Caki‐2/S cells, as previous studies have reported, 42 also concerning pathogenesis and sunitinib resistance in RCC 43–45 .…”
Section: Discussionmentioning
confidence: 79%
“… 36 , 37 In various tumour entities, aberrant activation of MET and AXL has been described in terms of resistance to RAS–RAF–MEK, mammalian target of rapamycin (mTOR), VEGFR therapies 16 , 38 , 39 including sunitinib and sorafenib, 16 , 40 and, recently, immune evasion. 41 The activity of c‐MET‐downstream kinases, ERK ½, and AKT/S6K might also be related to enhanced cell survival and proliferation in 786‐O/S and Caki‐2/S cells, as previous studies have reported, 42 also concerning pathogenesis and sunitinib resistance in RCC. 43 , 44 , 45 A distinct ability to overcome cell death is a further trait of sunitinib tolerance.…”
Section: Discussionmentioning
confidence: 88%